Students' satisfaction while engaging in UNIMAS mooc ICT competency course - Nor Shazmira, binti Zulkafli (Universiti Malaysia Sarawak (UNIMAS), 2015)
MOOC is a new phenomenon that has gained a lot of attention including in the high education system. Since semester 1 2014/2015, UNIMAS has developed its own MOOC which is ICT Competency course. This study examined the perception and satisfaction of UNIMAS students while enrolling in this course. There are two main categories of criteria in a MOOC which are pedagogical criteria and technical criteria. Pedagogical criteria consist of instructional design and assessment. For technical criteria, there are user interface, video content, learning and social tools and lastly, learning analytics. Data on students’ satisfaction (N=46) in these criteria were analysed using correlation analysis. There are significant relationships between all these criteria and the students’ satisfaction. These results highlight that each of the criteria play important role to ensure the satisfaction of students while they are enrolling in the course and therefore, make UNIMAS MOOC ICT Competency course one of the successful MOOC.